Raising the quality of teaching through Kyouzai Kenkyuu – the study of teaching materials. Issue 1 (3rd January 2017) - Sarkar Arani, Mohammad Reza
Abstract : Purpose: This study attempts to provide cross-cultural learning by focusing on a very important aspect of research, the study of teaching materials, known as Kyouzai Kenkyuu in Japan. The purpose of this paper is to investigate teachers' views and awareness about the study of teaching materials, in particular, the views and awareness of Iranian teachers, who are beginning to understand their teaching practice and professional development through lesson study. Design/methodology/approach: Qualitative research methods were employed for data collection. These methods included comparative analysis of an Iranian mathematics lesson from the perspective of Japanese educators and semi-structured interviews with all participants of the lesson analysis meetings. Findings: The findings are intended to position Kyouzai Kenkyuu as an important aspect of Japanese lesson study and to make explicit the beliefs and values that underpin and shape pedagogical reasoning that support researchers and practitioners to improve the quality of teaching through lesson study. This was achieved through post-lesson discussion meetings, and the beliefs and values were those the participants were largely unaware of but could be clarified through a cross-cultural comparison. For instance, Japanese teachers focus more on learners and the study of teaching materials for raising the quality of teaching, whereas Iranian teachers focus more on the content of teaching and teacher behavior. Research limitations/implications: This study delivers a transnational learning opportunity for teachers and researchers to learn how to provide evidence-based analysis of a lesson to raise the quality of teaching. However, as this is a case study and focuses specifically on Kyouzai Kenkyuu, it opens up the possibility for comparative analysis of more sample lessons and other aspects of Japanese lesson study. Practical implications: It may be interesting for teachers and researchers to see how such a study could help them revise their quality of teaching through lesson study and construct shared knowledge about how to teach and to clarify "the pedagogical theories" that underpin such knowledge building. Social implications: The value of this study is in its ability to reveal to educators their own unconscious teaching script and knowledge and "the pedagogical theories" that underpin such knowledge. It provides an opportunity for evidence-based critiques of our own teaching script, theory, view and values that we accept culturally, share tacitly and may not even be aware of in the construction process. Originality/value: This study combines careful measurement with an "insider's perspective" from Iran and an "outsider's perspective" from Japan of differing educational concepts within the same subject area. The objective is to provide a deeper understanding of the real world of lesson study and how it can help educators to construct shared knowledge about how to teach in practice and to support teachers to revise the cultural context of teaching.